Pengaruh Penanganan Kasus Korupsi Terhadap Aduan Masyarakat Kepada KPK - Zidni Robby Rodliyya; Vid Adrison (Integritas: Jurnal Antikorupsi, 2022)
Eradication of corruption in Indonesia requires public participation to be more effective and efficient. One aspect of community involvement when eradicating corruption is the reporting of suspected corruption crimes to law enforcers, including the Komisi Pemberantasan Korupsi (KPK). Public complaints are very important for the KPK when investigating corruption cases. Therefore, knowing which factors are correlated with the community's intention to report is important. To accommodate public complaints, the KPK has established a whistle-blower system. This study aims to determine the correlation between the handling of corruption by the Corruption Eradication Commission and the number of public complaints to the Corruption Eradication Commission pertaining to corruption crimes at the City and Regency levels throughout Indonesia. Case handling is proxied by the number of cases being investigated by the KPK compared to the number of complaints received by them. By using the panel system dynamic regression model GMM, the results of the study found that the ratio of handling cases of lag 1, the average democracy index, education level and the number of complaints of lag 1 were correlated significantly with the number of public complaints, while the lag 1 corruption ratio variable is not significantly correlated with public complaints.